Karakterisasi Flavonoid Antioksidan Dari Daun Jambu Biji (Psidium guajava L.) - Harrizul Rivai; Lisa Putriani; Mahyuddin Mahyuddin (Jurnal Farmasi Higea, 2010)
Flavonoid compounds have been isolated from guajava leaf from 100 grams of dried samples of guava leaf  were obtained liquid extract 130 mL, n-hexane fraction as much as 1.65 g, 1.95 g of chloroform fraction, fraction of 1.87 g ethyl acetate, butanol fraction of 2.15 g, and the remaining fraction as much as 28.96 g and flavonoid A as much as 36.9 mg. Flavonoid A is a yellow amorph form and decompose at a temperature of 190-192 C. Based on ultraviolet spectrum with various reagents shear and infrared spectrum, these compounds are known as flavonol-3-O-diglukosida. Flavonoids A provide antioxidant activity with the percent inhibition of 85.364% ± 0.2073%, while the flavonoid B 68.160%, ± 0.2073.